Graph coloring program of exam scheduling modeling based on bitwise coloring algorithm using python - Arifin, Samsul; Muktyas, Indra Bayu; Al Maki, Wikky Fawwaz; Mohd Khairul Bazli, Mohd Aziz (Science Publications, 2022)
A graph coloring is the process of assigning labels to the vertices of a graph in such a way that no two adjacent vertices have the same color. The chromatic number of a graph G is the smallest number of colors that can be assigned to it. Graph coloring has a wide range of applications and is commonly used to solve scheduling issues. In this article, the researchers design an algorithm and apply it to a computer program (Python) to solve graph coloring and to visualize the variation of exam scheduling modeling at Binus University in graphs based on the Bitwise Graph Coloring Algorithm. The researchers develop a graph coloring algorithm by considering some of the graph vertices to be binary numbers. Bitwise operations make this algorithm run very fast. The algorithm constructed by the researcher is a modification of Komosko, etc.’s algorithm in 2015 and it is the key result of this research. The researchers try to offer an alternative method in the process of making the final semester exam schedule. Next, the researcher tested the program on the data of subjects and students who took it at the Study program of TI-Stat-Math in Binus University. Our results show that from the program created and the simulations performed, 8 schedule slots are generated in about 0.675 sec.